2012
DOI: 10.1111/j.1834-7819.2012.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiologic effects of commercially available gel and powder containing Acacia arabica on gingivitis

Abstract: Background: There is a need for an anti-plaque agent that can be used on a daily basis without the side effects of antibacterial chemicals such as chlorhexidine. The present study was designed to evaluate the clinical and microbiologic effects of commercially available gel and powder containing Acacia arabica in subjects with gingivitis. Methods: One hundred and twenty subjects with chronic generalized gingivitis were selected and randomly divided into four groups: Group 1 -placebo group; Group 2 -Acacia arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
2
22
0
1
Order By: Relevance
“…Various other studies have allowed subjects to apply a pea‐sized amount of CHX gel on the teeth gums with the index finger and leaving it undisturbed for approximately 5 min before rinsing. This resulted in significant improvement (as evaluated in studies 6–24 weeks) over the placebo gel group on plaque scores and the gingival index . The outcome of these studies taken together with the result of this review indicates that CHX gel is not effective in combination with toothbrushing but is effective when applied with a finger to teeth and gums.…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies have allowed subjects to apply a pea‐sized amount of CHX gel on the teeth gums with the index finger and leaving it undisturbed for approximately 5 min before rinsing. This resulted in significant improvement (as evaluated in studies 6–24 weeks) over the placebo gel group on plaque scores and the gingival index . The outcome of these studies taken together with the result of this review indicates that CHX gel is not effective in combination with toothbrushing but is effective when applied with a finger to teeth and gums.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the mechanical removal of microbial plaque by scaling procedure with the added benefits of anti-inflammatory, astringent, and antimicrobial actions exerted by Periocare ® ingredients. In a similar study by Pradeep AR et al .,[11] the oral microbial load was found to be reduced after topical application of a herbal medicament containing mainly Acacia arabica . The results of our study also reported a reduction in the oral microbial flora in group I and group II subjects, which could be attributed to the antimicrobial action of various components of the test product used.…”
Section: Discussionmentioning
confidence: 75%
“…The PubMed-MEDLINE, Cochrane CENTRAL, IndMed, and other sources identified 1378 unique records which were screened by title and abstract [ Figure 2 ]. After full-text reading, 10 records[ 15 16 17 27 28 29 30 31 32 33 ] were excluded. This exclusion resulted in 19 full-text articles plus 3 unpublished records.…”
Section: Resultsmentioning
confidence: 99%